2020
DOI: 10.1200/jco.2020.38.15_suppl.3583
|View full text |Cite
|
Sign up to set email alerts
|

Results of a completed phase I trial of CBL0137 administered intravenously (IV) to patients (Pts) with advanced solid tumors.

Abstract: 3583 Background: The novel curaxin CBL0137 intercalates into DNA, interfering with histone/DNA binding. Consequent trapping of histone chaperone FACT leads to MYC, NF-kB, and HSF1 inhibition, p53 activation, and an IFN response. CBL0137 shows broad nonclinical antitumor activity (Gasparian et al. Sci Transl Med. 2011; 3(95):95ra74). Methods: This dose-ranging study assessed the CBL0137 maximum tolerated dose (MTD) and recommended Phase 2 dose (RP2D) and CBL0137 safety, pharmacokinetics (PK), and efficacy in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Crucially, both chromatin looping disruption and FACT complex trapping led to reduced expression of MYC family genes (Carter et al 2015;Kantidze et al 2019;Wang et al 2020). Although complete degradation of CTCF is lethal in normal cells (Moore et al 2012;Kemp et al 2014), curaxins were well tolerated in xenograft models across multiple cancer cell types (Dermawan et al 2016;Kim et al 2016;Barone et al 2017) and recently completed phase I clinical trials (Sarantopoulos et al 2020), making it a promising drug against MYC-addicted cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, both chromatin looping disruption and FACT complex trapping led to reduced expression of MYC family genes (Carter et al 2015;Kantidze et al 2019;Wang et al 2020). Although complete degradation of CTCF is lethal in normal cells (Moore et al 2012;Kemp et al 2014), curaxins were well tolerated in xenograft models across multiple cancer cell types (Dermawan et al 2016;Kim et al 2016;Barone et al 2017) and recently completed phase I clinical trials (Sarantopoulos et al 2020), making it a promising drug against MYC-addicted cancers.…”
Section: Discussionmentioning
confidence: 99%
“…CBL0137 has been trialed in humans as a monotherapy where the primary concern was a manageable combined thrombocytopenia/neutropenia occurring in 2 of the 83 patients treated. 39 These findings may represent an off-target effect as we noted that CBL0137 can induce both ZBP1-dependent and non-ZBP1-dependent cell death in bone marrow derived myeloid cells. Further study will reveal if these effects impact outcomes when CBL0137 is combined with ICB in the clinic.…”
Section: Cbl0137 the First Flipon Therapeuticmentioning
confidence: 86%
“…This includes human pancreatic cancer [ 145 ]; neuroblastoma [ 146 ]; glioblastoma [ 147 149 ]; extremity melanomas [ 150 ]; small cell lung cancer [ 151 , 152 ]; hepatocellular carcinoma [ 153 ]; leukemia [ 154 ]; and medulloblastoma [ 155 ]. Importantly, a phase 1 clinical trial result of CBL0137 from cancer patients with solid tumors was communicated at the ASCO 2020 Annual meeting [ 156 ]. This phase 1 is a dose-ranging study that assessed the CBL0137 maximum tolerated dose (MTD), recommended Phase 2 dose (RP2D), safety, pharmacokinetics (PK), and preliminary efficacy in adults with advanced treatment-refractory solid tumors.…”
Section: Tp53/p53mentioning
confidence: 99%
“…These authors concluded that CBL0137 administered via IV was generally well tolerated with manageable toxicities and predictable PK, and the MTD and RP2D were estimated at 540 mg/m2 due to myelosuppressive DLTs. Preliminary evidence of antitumor activity supports Phase 2 testing [ 156 ].…”
Section: Tp53/p53mentioning
confidence: 99%